Problem Based Learning Model Integrated Islamic Values with Mind Mapping Assessment to Improve Students' Creative Thinking Skills - Uyumatul Ummah; Evi Roviati; Mujib Ubaidillah (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
The Indonesian education system requires developing 21st-century skills, including creative thinking skills (CTS). Students' CTS is still low. The study aims to describe student learning activities, analyze students' creative thinking skills, and describe student responses by applying a the problem-based learning (PBL) model that integrates Islamic values with mind-mapping assessments. The research method uses a true-experimental design with a posttest-only control design. The research location is at SMAN 1 Dukupuntang, and the respondents are 30 students. The sampling technique was random sampling, the population of all IPA students in class X. The selected classes were class X IPA 1 as the experimental class and X IPA 2 as the control class. Data collection research includes observation sheets, mind mapping, and questionnaires. Data processing techniques are in the form of normality tests, homogeneity tests, and hypothesis tests. The results showed that the average value of student learning activities is 88, classified as very good. Applying the PBL model that integrates Islamic values with mind mapping assessments can significantly improve students' CTS with scores of Asymp Sig. (2-tailed) 0.000. Student responses are positive with a response scale interest category (67,8). The findings in this study are that students need more stimulation to integrate Islamic values with science during online learning. It can be concluded that the PBL model, integrated with Islamic values and mind mapping assessment, can improve students' creative thinking skills.